PENGARUH WAKTU PERENDAMAN SEBELUM SONIKASI TERHADAP KADAR ASIATIKOSIDA PADA EKSTRAK DAUN PEGAGAN AIR (HYDROCOTYLE VULGARIS L.) SECARA KROMATOGRAFI CAIR KINERJA TINGGI (KCKT) - Armon Fernando; Fadhilatun Khoiriyah (Ensiklopedia of Journal, 2023)
Pegagan air (Hydrocotyle vulgaris L.) is one of the plants used as medicine, one of the contents of pegagan air (Hydrocotyle vulgaris L.) is asiaticoida. Asiaticosides are known having antioxidant and neuroprotective activities. This research aims at finding out the effect of immersion time before sonication of pegagan air (Hydrocotyle vulgaris L.) toward the leaf extract on asiaticoside levels. Extractions parameters used are immersion time and sonication time. The asiaticoside level was analyzed using high performance liquid chromatography by column C-18, the mobile phase of methanol : water (70:30), flow rate of 1 ml/min and detected at wavelength 206 nm. Calibration curves were made by using a series of concentrations of 2-14 ppm with a regression equation y = 11656x + 142673. Optimum asiaticoside levels in pegagan air (Hydrocotyle vulgaris L.) leaf extract were obtained at the time of immersion for two hours with sonication time for 15 minutes. The asiaticoside level obtained in the extract of pegagan air (Hydrocotyle vulgaris L.) leaf was 0,1699 mg/10 mg extract with a percentage of 1.6842%.Keywords: Pegagan air, Asiaticoside, Immersion, Sonication, HPLC.